The impact of anti-Russian sanctions on the export of Kazakhstan’s oil - Ongdash, А.; Omirtay, А.; Bekmukhametova, А. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
On the basis of the conducted study of the peculiarities of the state policy of the oil refining industry, it has been determined that the oil refining industry occupies a significant part of the country’s fuel and energy complex, providing for the needs of the economy of the Republic of Kazakhstan. At the same time, in the conditions of the global economy, Kazakhstan's oil-producing industry is experiencing problems due to anti-Russian sanctions, which make it difficult to implement the national policy of overcoming the raw orientation of the export of oil and oil products. The very fact of the presence of anti-Russian sanctions forms the field of intensifying competition between Russia and Kazakhstan in the European energy market and creates conditions for the use of methods of imperfect competition, for the use of political instruments in solving economic problems. This situation has a negative impact on the development of the oil production industry in both Russia and Kazakhstan, and requires its resolution, which becomes possible when the Kazakh oil sector moves to an innovative model of development based on the intensification of oil refining. Sanctions against Russia create significant difficulties due to the fact that Kazakhstan uses Russian transport infrastructure to trade with European Union countries. Therefore, the Republic of Kazakhstan needs to strive to reduce economic costs by insuring the transportation process of exported goods and subsidizing some additional costs. Kazakhstan is taking the initiative in mediating between the countries, trying to maintain relations with Russia through diplomacy, which it has conducted so far, as well as coping with the economic difficulties and political pressure that the country is facing in a balanced way. Thus, Kazakhstan continues its traditional multi-vector foreign policy strategy. Of course, the most effective and comprehensive solution for Kazakhstan, as well as for all countries in the region, is to end the war in Ukraine as soon as possible.